Access to flexible working and informal care - Mark L. Bryan (University of Essex, Institute for Social and Economic Research (ISER), 2011)
We use matched employer-employee data to explore the relationship between employees' access to flexible working arrangements and the amount of informal care they provide to sick or elderly friends and relatives. Flexitime and the ability to reduce working hours are each associated with about 10% more hours of informal care, with effects concentrated among full-time workers providing small amounts of care. The wider workplace environment beyond formal flexible work also appears to facilitate care. Workplaces do not respond to the presence of carers by providing flexible work, instead there is some underlying selection of carers into flexible workplaces.
Keywords: D13; J22; J29; 330; informal care; flexible work; matched employer-employee data; Arbeitsbeziehungen; Arbeitszeitgestaltung; Flexibilität; Soziale Beziehungen; Pflegebedürftigkeit; Großbritannien